Association Between Tumor Mutation Burden (TMB) and Outcomes of Cancer Patients Treated With PD-1/PD-L1 Inhibitions: A Meta-Analysis - Zhu, Jiaxin; Zhang, Tiantian; Li, Jiahao; Lin, Junming; Liang, Wenhua; Huang, Wenjie; Wan, Ning; Jiang, Jie (Frontiers in Pharmacology, 2019)
Background: Programmed cell death 1(PD-1) or programmed cell death ligand 1(PD-L1) inhibitions are being strongly recommended for the treatment of various cancers, while the efficacy of PD-1/PD-L1 inhibitions varies from individuals. It is urgent to explore some biomarkers to screen the most appropriate cancer patients. Tumor Mutation Burden (TMB) as a potential alternative has been drawing more and more attention. Therefore, we conducted a meta-analysis to quantitatively explore the association between TMB and outcomes of PD-1/PD-L1 inhibitions. Methods: We searched eligible studies that evaluated the association between TMB and the outcomes of PD-1/PD-L1 inhibitions from PubMed, Embase, Cochrane database up to October 2018. The primary endpoints were the progression-free survival (PFS) and the overall survival (OS) in patients with high TMB or low TMB. The pooled hazard ratios (HR) for PFS and OS were performed by Stata. Results: In this analysis, a total of 2,661 patients from eight studies were included. Comparing PD-1/PD-L1 inhibitions to chemotherapy, the pooled HR for PFS and OS in patients with high TMB was 0.66 (95% confidence interval (CI) 0.50 to 0.88; P=0.004) and 0.73 (95% CI 0.50 to 1.08; P=0.114) respectively ; while the pooled HR for PFS and OS in patients with low TMB was 1.38 (95% CI 0.82 to 2.31; P=0.229) and 1.00 (95% CI 0.80 to 1.24; P=0.970) respectively . Meanwhile, comparing patients with high TMB to patients with low TMB, the pooled HR for PFS in patients treated with PD-1/PD-L1 inhibitions was 0.47 (95% CI 0.35 to 0.63; P=0.000). Patients with high TMB showed significant benefits from PD-1/PD-L1 inhibitions compared to patients with low TMB. Conclusion: Despite the present technical and practical barriers, TMB may be a preferable biomarker to optimize the efficacy of PD-1/PD-L1 inhibitions.